MAPPING PRIORITIES IN PRODUCT DESIGN:: STUDENT INSIGHTS ON COURSE CONTENT AND PROFESSIONAL RELEVANCE. - Aston, Jeremy; Barbosa, Luciana; Gomes, Marco (Design/Arts/Culture, 2025)
This article presents findings from the 2023 survey titled "Study Futures for Product Design," conducted by three faculty members from ESAD College of Art and Design. The survey aimed to gather and analyse insights from one hundred undergraduate and postgraduate students regarding their experiences and expectations within their product design education. This research was motivated by ongoing observations within ESAD’s Master's program in Product Design, as well as contemporary studies on design education for the 21st century by scholars such as Michael Meyer and Don Norman. The findings underscore the evolving nature of design education, particularly the need for curricular adjustments that align more closely with the demands of the modern professional landscape. By emphasising student feedback, this article advocates for a reevaluation of current pedagogical approaches, aiming to better prepare students for the diverse and dynamic challenges of the design industry. The study calls for a shift in focus towards teaching content that enhances relevance to professional applications and optimises employment opportunities in the field of product design and related industrial specialisations.